PENERAPAN FISHFINDER DAN PENGERING IKAN BAGI NELAYAN TANGKAP DI KELURAHAN MALABERO TELUK SEGARA KOTA BENGKULU - irkhos irkhos irkhod; M. Ginting; Nanang Sugianto (Universitas Bengkulu, 2018)
Implementation of Fish-finder and Fish dryer for Fishermen in Malabero Teluk Segara Bengkulu City aims to apply appropriate technology. After all, this activity is expected to increase the efficiency and quality of dried fish as well as more catch and decreasing operational cost. Community service activity is implemented by training method. Through this activity we have produced the product of fish dryers and guidance of fish-finder use to determine fish position. Fish dryers amounted to 2 pieces of iron with each dimension of the same height 1.5 m long 1.8 m and width of 0.8 m. One tool has 3 (three) drying racks with a total wide of 3.84 m2 with a tool capacity of approximately 20 kg of wet fish. The maximum temperature in the dryer room reaches 60°C, and the time taken to dry the wet fish at a maximum temperature is about 8 hours. Keywords: fish-finder, fish dryer, efficiency, quality